A modelling study of segmentation of naturally ventilated tall office buildings in a hot and humid climate - Liu, Pei-Chun (2012)
The prevailing paradigm in indoor environment control of office buildings often excludes natural ventilation, due to the fact that its dynamic nature may not be compatible with the close control of mechanical conditioning systems. The challenges will be greater in terms of the potential high magnitudes of wind and buoyancy forces at high levels of tall buildings. This research is concerned with the prospect of tall office buildings that are purely naturally ventilated. It is proposed that “segmentation” might offer the least risky approach for natural ventilation design of non-domestic tall buildings. Accordingly, the generic design procedure are proposed for investigating the influence of segmentation on ventilation air flows: firstly, the single-cell envelope flow model is adopted to evaluate the steady-state bulk flows through openings under a specified design condition; secondly, dynamic thermal modelling with an air flow network module is used, because of the particular importance of the coupling between the airflow and thermal process for evaluating the year-round ventilated cooling potential of targeted spaces. The chosen thermal model utilizes a multi-cell airflow network model (AFN) since the targeted buildings can no longer be described by a single-cell model; thirdly, computational fluid dynamics (CFD) simulation is suggested in the later design stage to cope with insufficient resolution of local airflow distribution in previous modelling stages; finally, the overall performance of comfort ventilation is then interpreted in relation to adaptive thermal comfort theory by the use of Building Bioclimatic Charts, which offers a way of rapidly testing whether or not natural ventilation is likely to produce comfortable conditions. The novelty of this work lies not in the methodology, which uses available modelling tools, but in the evaluation of naturally ventilated tall buildings with reference to segmentation in the climatic context of Taiwan. The effect of segmentation is evaluated by comparing the overall ventilation performance under three different building configurations, namely the isolated, segmented and non-segmented tall buildings. The overall objectives are to determine whether the magnitudes of air flow rates and the resultant flow velocity can achieve the desired comfort ventilation over a range of specified conditions. Potential scenarios where the design goals may not be ensured are identified. The feasibility for naturally ventilated tall office buildings in hot and humid climates is clarified accordingly.